Unsteady laminar mixed convection boundary layer flow near a vertical wedge due to oscillations in the free-stream and surface temperature - Hossain, Anwar; Roy, N.C.; Hussain, S. (Zielona Góra: Uniwersytet Zielonogórski)
The unsteady laminar boundary layer characteristics of mixed convection flow past a vertical wedge have been investigated numerically. The free-stream velocity and surface temperature are assumed to be oscillating in the magnitude but not in the direction of the oncoming flow velocity. The governing equations have been solved by two distinct methods, namely, the straightforward finite difference method for the entire frequency range, and the extended series solution for low frequency range and the asymptotic series expansion method for high frequency range.
Keywords: mixed convection; boundary layer flow; vertical wedge; free-stream oscillation